Assessing the impact of wildfires on water quality using satellite remote sensing: the Lake Baikal case study - Pinardi, Monica; Stroppiana, Daniela; Caroni, Rossana; Parigi, Lorenzo; Tellina, Giulio; Free, Gary; Giardino, Claudia; Albergel, Clément; Bresciani, Mariano (Frontiers in Remote Sensing, 2023)
Lakes have been observed as sentinels of climate change. In the last decades, global warming and increasing aridity led to an increase in both the number and severity of wildfires. This have a negative impact on lake catchments by reducing forest cover and triggering cascading effects in freshwater ecosystems. In this work we have used satellite remote sensing to analyse potential fire effects on lake water quality of lake Baikal (Russia), considering the role of runoff and sediment transport, a less studied pathway compared to fire emissions transport. The main objectives of this study were to analyse timeseries and investigate relationships among fires (i.e., burned area), meteo-climatic parameters and water quality variables (chlorophyll-a, turbidity) for the period 2003-2020. Because Baikal is oligotrophic, we expected detectable changes in water quality variables at selected areas near the three mains tributaries (River Selenga, River Barguzin and River Angara), due to river transport of fire-derived burned material and nutrients. Timeseries analysis showed seasonal (from April to June) and inter-annual fire occurrence, precipitation patterns (high intensity in summer) and no significant temporal changes for water quality variables during the studied periods. The most severe wildfires occurred in 2003 with the highest burned area detected (36767 km2). The three lake sub-basins investigated have shown to respond differently according to their morphology, land cover types and meteo-climatic conditions, indicating their importance in determining the response of water variables to the impact of fires. Overall, our finding suggests that lake Baikal shows resilience in the medium-long term to potential effects of fires and climate change in the region.